2017
DOI: 10.5194/bg-14-1617-2017
|View full text |Cite
|
Sign up to set email alerts
|

C  ∕ N ratio, stable isotope (<i>δ</i><sup>13</sup>C, <i>δ</i><sup>15</sup>N), and <i>n</i>-alkane patterns of brown mosses along hydrological gradients of low-centred polygons of the Siberian Arctic

Abstract: Abstract. Mosses are a major component of the arctic vegetation, particularly in wetlands. We present C ∕ N atomic ratio, δ13C and δ15N data of 400 brown-moss samples belonging to 10 species that were collected along hydrological gradients within polygonal mires located on the southern Taymyr Peninsula and the Lena River delta in northern Siberia. Additionally, n-alkane patterns of six of these species (16 samples) were investigated. The aim of the study is to see whether the inter- and intraspecific differenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Biplot of δ 13 C and TOC/TN (total organic carbon/total nitrogen) from SAM18‐01 bulk organic matter (green dots). Colourized rectangles for comparison; POC 1 = particulate organic carbon measured from fluvial samples of the Lena Delta (Winterfeld et al ., 2015), Moss 2 from the central Lena Delta (Zibulski et al ., 2017), lake algae 3 and SOM 3 = soil organic matter from Transbaikalia (Prokopenko et al ., 1993), LD 4 = Lena Delta Yedoma (MIS 3–2) and Holocene cliff exposure (Wetterich et al ., 2008, 2020), W‐LD 5 = western Lena Delta fluvial deposits (MIS 3–2) from cliff exposure (Schirrmeister et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biplot of δ 13 C and TOC/TN (total organic carbon/total nitrogen) from SAM18‐01 bulk organic matter (green dots). Colourized rectangles for comparison; POC 1 = particulate organic carbon measured from fluvial samples of the Lena Delta (Winterfeld et al ., 2015), Moss 2 from the central Lena Delta (Zibulski et al ., 2017), lake algae 3 and SOM 3 = soil organic matter from Transbaikalia (Prokopenko et al ., 1993), LD 4 = Lena Delta Yedoma (MIS 3–2) and Holocene cliff exposure (Wetterich et al ., 2008, 2020), W‐LD 5 = western Lena Delta fluvial deposits (MIS 3–2) from cliff exposure (Schirrmeister et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Individual samples with high TOC/TN are associated with drift wood particles (Meyers & Teranes, 2001). Typical values of moss (Zibulski et al ., 2017) as known from the central delta (Samoylov Island) or POC (particulate organic carbon) as known from river water sampling (Winterfeld et al ., 2015) are not met with SAM18‐01 bulk organic matter. This is also true for Transbaikal lake algae (Prokopenko et al ., 1993), which all have lighter isotope signatures with δ 13 C < −29‰.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that, as carbon isotope discrimination in Sphagnum is related to water retention capacity, the signal becomes more apparent under drier conditions (Williams & Flanagan, 1996); the signal may thus lose part of its significance towards the wetter end of the range. Assuming that these extremely wet signatures indicate submersed Sphagnum, there may be a complex origin of plant-available carbon from varying dissolved inorganic carbon sources, some of which could have been enriched in the heavy isotope ("hard-water effect"), making it difficult to interpret the values of Sphagnum samples with small "apparent" discrimination (Hammarlund et al, 1997;Zibulski et al, 2017).…”
Section: Paleoecological Methodologymentioning
confidence: 99%
“…Short-term culturing experiments documenting this symbiosis using 13 C-labelled CH4 have shown that conservatively 30% to 40% of C in new biomass in Sphagnum and Scorpidium, respectively, is derived from CH4 15,16 . CH4-derived C is most strongly incorporated in submerged mosses (compared to nonsubmerged mosses) regardless of the species 15,42,43,46 . Using a C isotope mass balance model, we estimate that during the middle Holocene up to ~25% of the C in aquatic moss waxes at TS was derived from CH4 (Extended Data Fig.…”
Section: Evidence For Changes In Methane Cycling At Tsmentioning
confidence: 99%
“…A symbiotic relationship between both Sphagnum (Class: Sphagnopsida, Family: Sphagnaceae) and brown mosses and methanotrophic bacteria is well-documented 15,16,41 . Mossassociated methane-oxidizing bacteria (MAMO) form dense colonies within moss cells and on moss surfaces 16 , where they oxidize CH4 using O2 produced during photosynthesis, and in turn provide the moss CO2 and H2O 15,16,42,43 . Data from Siberian ponds has demonstrated that 60-99% of the CH4 produced by sedimentary methanogens in anoxic ponds is oxidized within aquatic brown moss layers, 44 demonstrating MAMO are highly efficient at consuming CH4 in the water column.…”
Section: Evidence For Changes In Methane Cycling At Tsmentioning
confidence: 99%